Crisis communication: Theoretical perspectives and dynamics of a complex concept - Matías, Ana; Cardoso, Luís (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
This article analyzes the evolution of the concept of crisis within the organizational scope, and the responses that can be given by crisis communication. Our objectives include a historical approach to organizational management, that has recognized the importance of having a plan to face crisis and communicate effectively with the stakeholders. The concept of crisis has changed how organizations respond internally and externally. We conclude that organizations can react with a structured plan to unexpected situations, combining crisis management principles with accurate and targeted communication.